Peran Stakeholder terhadap Program Kesehatan Jiwa dalam Penanggulangan Pasung pada Orang dengan Gangguan Jiwa (ODGJ) di Kecamatan Moyudan Kabupaten Sleman (Berita Kedokteran Masyarakat (BKM), 2020)
Purpose: Physical restraint of mental illness (pasung) has been widely documented in Indonesia. However, there is still a lack of studies exploring the role of puskesmas in eliminating pasung. This study aims to document the head of the puskesmas in advocating for and working with local administrators to build a positive climate of involving people with mental illness in productive activities so that they have no reason to be confined at home.Methods: This case study was based on in-depth interviews of 19 community health center workers and community personnel, field observations, and document review.Results: Periodic, regular communication organized in simple meetings and field visits with local stakeholders can open up stakeholders and have the same vision in public health. With hospitable visits of respected local officials and health workers, families and communities, who at first were ashamed and isolated their mentally ill family members, are now becoming open-minded and participating in programs for persons with mental illness.Conclusion: Communication and public health leadership skills from the head of puskesmas are essential skills in inviting local administrators to work together for public health.